Renal expression of heat shock proteins after brain death induction in rats. - Bos, E; Schuurs, T; Kraan, M; Ottens, P; van den Eijnden, MM; Leuvenink, H; Kampinga, H; van Goor, H; Ploeg, R (2005)
The majority of transplanted kidneys are derived from brain-dead patients. This nonphysiological state influences the hemodynamic and hormonal status of the donor. As a result, kidneys derived from brain-dead donors have inferior graft survival and increased graft function loss. Heat shock proteins (HSPs) are a family of stress-inducible proteins involved in maintaining cell homeostasis and regulating the immune system. We studied renal expression of the genes HO-1, HSP27, HSP40, and HSP70 after experimental brain death in rats. Brain death was induced in male F344 rats by slowly inflating a balloon catheter in the epidural space. Untreated rats were used as controls. Animals were humanely killed after 4 hours of brain death. Kidneys were analysed using RT-PCR, Western blotting, and immunohistochemistry. RT-PCR showed an increase in expression of genes coding for HO-1 (3.6-fold; P < .05) and HSP70 (2.7-fold; P < .05) after brain death. Western blotting also revealed an increase in HO-1 protein levels (4.6-fold; P < .001) but changes in HSP70 protein expression were not detected. Immunohistochemistry showed increments of HO-1 protein expression in the renal cortical tubules of brain-dead rats. HSP70 was predominantly increased in renal distal tubules of brain-dead rats treated for hypotension. No changes were observed in renal HSP27 and HSP40 expression after brain death. Renal stress caused by brain death induces expression of the cytoprotective genes HO-1 and HSP70, but not of HSP27 and HSP40. The up-regulation of these cytoprotective genes could be part of a recuperative mechanism induced by stress associated with brain death.